THE EFFECT OF MENTAL ACCOUNTING ON STUDENT’S INVESTMENT DECISIONS: A STUDY AT INVESTMENT GALLERY (GI) FEB UNIVERSITY OF BENGKULU AND SYARIAH INVESTMENT GALLERY (GIS) FEB IAIN BENGKULU - Fitri Santi; Nelsi Valetta Sahara; Kamaludin Kamaludin (Jurnal Ilmiah Ekonomi Bisnis, 2019)
Our study tries to explore the existence of mental accounting (MA) phenomenon among the investors at Investment Gallery FEB University of Bengkulu and the investors at Sharia Investment Gallery FEB IAIN Bengkulu, and to test its influences on the stock investment decision. We collect data using questioner. This study uses simple linear regression analysis to test the hypothesis. The results show that investors do have the MA. The average respondents' answers indicate that they treat monthly money with bonus money differently in investing while using monthly money as the capital, they averagely use a smaller portion of their monthly money for investment, but when the capital is their bonus money, then they use more portion of the money for the investment. For the respondents, their monthly money is more important than the bonus money, and they are also more afraid of the risks of investing the monthly money than investing the bonus money, and when there is a loss, the regret level of losses from investing monthly money is higher than regret level of losses from investing bonus money. The result shows the MA exists among the investors, and have a significant effect on the stock investment decisions.